The role of prophage in plant-pathogenic bacteria - Varani, Alessandro M. [UNESP]; Monteiro-Vitorello, Claudia Barros; Nakaya, Helder I.; Van Sluys, Marie-Anne (Annual Reviews, 2013)
A diverse set of phage lineages is associated with the bacterial plant-pathogen genomes sequenced to date. Analysis of 37 genomes revealed 5,169 potential genes (approximately 4.3 Mbp) of phage origin, and at least 50 had no function assigned or are nonessential to phage biology. Some phytopathogens have transcriptionally active prophage genes under conditions that mimic plant infection, suggesting an association between plant disease and prophage transcriptional modulation. The role of prophages within genomes for cell biology varies. For pathogens such as Pectobacterium, Pseudomonas, Ralstonia, and Streptomyces, involvement of prophage in disease symptoms has been demonstrated. In Xylella and Xanthomonas, prophage activity is associated with genome rearrangements and strain differentiation. For other pathogens, prophage roles are yet to be established. This review integrates available information in a unique interface (http://propnav.esalq.usp.br) that may be assessed to improve research in prophage biology and its association with genome evolution and pathogenicity. © Copyright ©2013 by Annual Reviews. All rights reserved.
Keywords: Bacteriophage; Genome evolution; Genome plasticity; Mobile genetic elements; Plant-pathogen interaction; Recombination